EFFECTIVE DOSE FOR RADIOLOGICAL PROCEDURES IN AN EMERGENCY DEPARTMENT: A CROSS-SECTIONAL STUDY. Issue 1 (5th March 2020) - Naseri, Maryam; Shahsavan, Mohammad; Salahshour, Faeze; Peiman, Soheil; Allameh, Seyed Farshad; Farzanehfar, Saeed; Emami-Ardekani, Ali Reza; Pouraliakbar, Hamidreza; Abbasi, Mehrshad
Abstract: The extent of radiation exposure in emergency settings is not well documented; here, the corresponding effective dose (ED) is provided. In 500 patients admitted in row to the emergency department, ED was compared in patients according to complaints and their visiting physicians. Out of all, 220 patients aged 43.5 ± 22.2 years (admission: 2.0 ± 1.6 days) had at least an imaging. The main reasons for admission were trauma (10.5%) and then orthopedic problems (8.6%). EDs from CT and radiography were 1.66 ± 3.59 and 0.71 ± 1.67 mSv, respectively (from all 2.29 ± 4.12). Patients with abdominal (5.8 ± 5.2 mSv; p  < 0.002) and pelvic (12.0 ± 6.3 mSv; p  < 0.007) complaints received higher ED from CT and radiography and, also, patients visited by surgeons (7.94 ± 6.9 mSv). CT scan was the main source for ED to patients. Irrespective of the final diagnosis, patients with abdominopelvic complaints and those visited by surgeons are at higher exposure risk.